A method for the geometric standardization of intraoral radiographs for long-term follow up of replanted teeth: A case report - Hamanaka, Elizane Ferreira [UNESP]; Poi, Wilson Roberto [UNESP]; Salzedas, Leda Maria Pescinini [UNESP]; Alves, Lucieni Campoli [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Sonoda, Celso Koogi [UNESP]; Martins, Christine Men [UNESP] (Wiley, 2013)
The interpretation of the set of radiographs taken during the follow-up period after tooth replantation might pose several difficulties, especially the inability to adequately reproduce the projection geometry of the exposures. This article describes a method for the geometric standardization of intraoral radiographs using a custom-made apparatus comprising a film-holder attached to an occlusal splint for the long-term follow up of dentoalveolar trauma. The method was applied in a patient who suffered an avulsion of the maxillary central incisors and had the teeth replanted after 4 h in saline storage. Endodontic treatment started 7 days after the trauma with changes of a calcium hydroxide intracanal medication every 15 days in the first 2 months and thereafter at 30-day intervals for 8 months. Root canal filling was carried out after this period. The radiographic exposures taken at the follow-up visits were standardized to identify the possible alterations during the repair process, such as root resorptions. A maxillary arch impression was made with alginate, and the model was cast in stone for fabrication of an acetate occlusal splint. The custom-made apparatus used for standardization of the radiographic exposures was fabricated by fixing a Rinn X-C-P film-holder and a 5-mm-long piece of 0.7-mm orthodontic wire to the occlusal splint with autopolymerized acrylic resin. Radiographs were taken at 4-month intervals, starting 10 months after replantation up to 76 months. The images were digitized and analysed using the Digora system. The length of the central incisors was determined to verify the reproduction of the projection geometry of the exposures and the orthodontic wire served to assess accuracy during length estimations in the radiographs. The method described in this article for geometric standardization of intraoral radiographs provided a consistent reproduction of the geometric exposure parameters, being indicated for use in the radiographic follow up of cases of dentoalveolar trauma. © 2012 John Wiley & Sons A/S.
Keywords: Dentoalveolar trauma; Radiographic standardization; Tooth avulsion; Tooth replantation